Considerations for designing socially assistive robots for older adults - Olatunji, Samuel A.; Falcon, Veronica; Ramesh, Anjali; Rogers, Wendy A. (Frontiers in Robotics and AI, 2025)
Social robots have the potential to support the health activities of older adults. However, they need to be designed for their specific needs; be accepted by and useful to them; and be integrated into their healthcare ecosystem and care network. We explored the research literature to determine the evidence base to guide design considerations necessary for socially assistive robots (SARs) for older adults in the context of healthcare. We identified various elements of the user-centered design of SARs to meet the needs of older adults within the constraints of a home environment. We emphasized the potential benefits of SARs in empowering older adults and supporting their autonomy for health applications. We identified research gaps and provided a road map for future development and deployment to enhance SAR functionality within digital health systems.